Aktualisasi Pendidikan Karakter Dalam Pembelajaran PAI di Sekolah Dasar - Raju Sanjani Sihombing; Iis Arifudin; Syakur Wildan (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
Character education in the world of education is very important in measuring the moral development of students in school. This is a provision for the future when living in a community environment. Character education begins with the way of thinking and behaving that each individual has within the scope of his life as values ​​in thinking and behavior that encourage individuals to have an attitude of responsibility for what they have done. The aim is to be able to bring about changes in the behavior of quality students and be able to achieve their goals in the learning process. Apart from that, students can be pioneers in implementing good character so that other friends can emulate them. It is very important to do this every day with routine and sincerity so that it becomes a good habit. This type of research is qualitative research. Qualitative research is research that explains phenomena or symptoms in detail and provides responses to research subjects. The results of this research explain that character education implemented in the independent curriculum education unit has been determined in the Pancasia Student Profile which includes having faith and devotion to God Almighty, global diversity, mutual cooperation, independence, critical reasoning and creativity. So teachers of Islamic Religious Education and Character Education subjects must provide a form of character education in PAI lessons to achieve success in the learning process. These forms are discipline, devotion, honesty, self-awareness, responsibility and empathy. Then, there are two steps that must be used to achieve success in achieving character education properly and correctly as an effort to form the morality of wise and wise students. These steps take the form of habituation and supervision.